Psychological needs of siblings of individuals with autism across life stages - Justiniani, Ma. Lourdes Isabel H. (Animo Repository, 2024)
Siblings of individuals with Autism Spectrum Disorder have varied and changing psychological needs throughout their lifetime. Semi-structured interviews with 15 siblings from various developmental stages were conducted, then thematic analysis was used to create a framework outlining the psychological needs of siblings and describing how these needs manifest in each developmental stage. This framework of psychological needs was compared to previously published research on siblings from different life stages. It was found that cultural and family values largely influence siblings’ psychological needs as well as how they see their brother or sister with ASD. Need satisfaction plays a pivotal role in the siblings’ well-being as well as the quality of their relationship with the individual with ASD. Additionally, there is still a need for more awareness, acceptance, and governmental and institutional support for individuals with ASD in the Philippines and for their families.